Kariera według młodych, czyli nowy paradygmat kariery na dysonansowym rynku pracy - Piorunek, Magdalena (Wydawnictwo Naukowe UAM, 2016)
A Career According to Young People, or a New Career Paradigm in the Dissonant Labour Market is an attempt at answering a question about an extent to which a narrative surrounding the specific features of the postmodern careers has been shared by the young adults who, being in the process of moving from the educational to the labour markets, have experienced these changes, to what extent they have internalised the career patterns emerging in the free-market reality that are different from those existent in Poland twenty-five years ago, and about what (new?) career paradigm is developed by the students. The paper presents preliminary results of a sampling carried out among young university students of the humanities who expressed their opinions on how vocational careers are defined and what associations they evoke. The article moreover provides personal examples of career development and discusses vocational catalysts and inhibitors of a career. The young university students did not, however, fully internalise the postmodern patterns of the mosaic careers prevailing in the competitive labour market, and simultaneously noticed a number of ambivalences and dissonances present in this market reality.
A Career According to Young People, or a New Career Paradigm in the Dissonant Labour Market
Keywords: vocational career; career patter; labour market; young university students; sampling